HUBUNGAN DUKUNGAN KELUARGA DAN AKTIVITAS FISIK DENGAN KUALITAS HIDUP PADA LANSIA DENGAN HIPERTENSI DI PUSKESMAS COLOMADU II KABUPATEN KARANGANYAR - prayuda yuli herlambang herlambang; Indriyati Indriyati; Vitri Dyah Herawati (Universitas Sahid Surakarta, 2023)
ABSTRACT Elderly is someone over 60 years old and unable to make a living daily.Hypertension is a degenerative disease that arises due to the transition in the elderly due to organ degradation and physical deterioration, so it impacts the quality of life of the elderly. To determine the correlation between family support and physical activity with quality of life in the elderly with hypertension at the Colomadu II Health Center in Karanganyar Regency.The study design was cross-sectional. The population were 262 elderly. The sampling technique used a purposive sampling of 158 samples. The research location is Colomadu II Health Center in Karanganyar Regency. Analysis of research data using logistic regression multivariate test. The most family support is elderly with good family support with 82 people (51.9%). Most physical activity is light with 66 people (41.8%). The highest quality of life is moderate with 64 people. There is a relationship between family support and quality of life in the elderly (p value 0.031), There is a relationship between physical activity and quality of life in the elderly with hypertension at the Colomadu II Health Center, Karanganyar Regency (p value 0.007). Physical activity has a 3.962 times closer relationship with quality of life.Physical activity has a 3.962 times closer relationship with quality of life in the elderly with hypertension at the Colomadu II Health Center, Karanganyar Regency (p value 0.007). Keywords: Family support, Physical activity, Quality of life, Elderly